Crude oil exposure of early life stages of Atlantic haddock suggests threshold levels for developmental toxicity as low as 0.1 μg total polyaromatic hydrocarbon (TPAH)/L. (May 2023) - Sørhus, Elin; Sørensen, Lisbet; Grøsvik, Bjørn Einar; Le Goff, Jérémie; Incardona, John P.; Linbo, Tiffany L.; Baldwin, David H.; Karlsen, Ørjan; Nordtug, Trond; Hansen, Bjørn Henrik; Thorsen, Anders; Donald, Carey E.; et al.
Abstract: Atlantic haddock ( Melanogrammus aeglefinus ) embryos bind dispersed crude oil droplets to the eggshell and are consequently highly susceptible to toxicity from spilled oil. We established thresholds for developmental toxicity and identified any potential long-term or latent adverse effects that could impair the growth and survival of individuals. Embryos were exposed to oil for eight days (10, 80 and 300 μg oil/L, equivalent to 0.1, 0.8 and 3.0 μg TPAH/L). Acute and delayed mortality were observed at embryonic, larval, and juvenile stages with IC50  = 2.2, 0.39, and 0.27 μg TPAH/L, respectively. Exposure to 0.1 μg TPAH/L had no negative effect on growth or survival. However, yolk sac larvae showed significant reduction in the outgrowth (ballooning) of the cardiac ventricle in the absence of other extracardiac morphological defects. Due to this propensity for latent sublethal developmental toxicity, we recommend an effect threshold of 0.1 μg TPAH/L for risk assessment models. Graphical abstract: Unlabelled Image Highlights: Haddock embryos exposed to medium concentrations of oil had reduced survival. The lowest exposure concentration impacted heart development, but not survival. The adverse effect threshold in risk assessment should be set to 0.1 μg TPAH/L.